Semiotic Analysis of Curative Preservation in the Jaran Kepang Art Tradition of Temanggung, Central Java - Iftitah, Nur 'Aini; Kamiliya, Rahadatul ‘Aisy; Karina, Aulia Citra Nur Sakinah; Rosa , Surya Ningtyas; Kurniasih , Yuni Pratiwi (Knowledge Garden: International Journal of Library Studies, 2024)
Art is a skill in creating a quality of work. Indonesia itself is famous for its many arts from Sabang to Merauke. The number of arts that exist around the community makes every region in Indonesia have dances, paintings, or carvings typical of their respective regions, especially in the Java Island area there is the art of Kuda Lumping. Kuda Lumping art performance commonly called Jaran Kepang is one of the original Indonesian traditional arts originating from Temanggung Regency, Central Java. This art is a featured art in Temanggung which is marked by the Jaran Kepang statue located in the eastern district park. Along with its development, the Jaran Kepang Temanggung dance no longer features stories about Diponegoro soldiers that characterize this dance. Some cultural initiators in Temanggung have modified the dance to include elements of Balinese art. Therefore, preservation is a fitting way to preserve and maintain an object or thing that does require protection, care, or preservation in the hope that the information remains. This research aims to preserve the performing arts of Jaran Kepang Temanggung with curative preservation through visual media, namely photography. This research uses a qualitative descriptive approach method that aims to describe fully and deeply about various phenomena studied and the use of semiotic analysis techniques. The results of this research will be in the form of a photo presentation of the visual preservation of jaran kepang which is useful to facilitate the delivery of messages from the photo of jaran kepang itself. Although this cultural heritage has begun to compete fiercely with the influx of foreign cultures and arts, this dance still shows high appeal and becomes a performance that captivates the hearts of its audience. In this case, the protection and preservation of the art of jaran kepang is needed so that it will always be recognized by future generations.